Effect of aerobic exercise, slow deep breathing and mindfulness meditation on cortisol and glucose levels in women with type 2 diabetes mellitus: a randomized controlled trial - Obaya, Hany Ezzat; Abdeen, Heba Ahmed; Salem, Alae Ahmed; Shehata, Mai Ali; Aldhahi, Monira I.; Muka, Taulant; Marques-Sule, Elena; Taha, Mona Mohamed; Gaber, Marwa; Atef, Hady (Frontiers in Physiology, 2023)
Background: Aerobic exercise combined with breathing exercises can be an integral part of diabetes mellitus treatment. This single-center, randomized, parallel-group study investigated the effect of the combination of aerobic exercise with slow deep breathing and mindfulness meditation on the glucose and cortisol levels of women with type 2 diabetes mellitus (T2DM). Materials & Methods: Fifty-eight middle-aged women with T2DM (mean age: 45.67 ± 2.92 years) were randomly assigned to either the aerobic training group (AT: n=29; mean age [46.1 ± 2.7 years]) or the aerobic exercise combined with slow deep breathing and mindfulness meditation (AT+DMM: n=29; mean age [45.24 ± 3.14 years]). Aerobic exercise was performed at 60–75% of the maximum heart rate. The women in each group were asked to perform the training three times weekly over a six-week period. The duration of each session was 40 minutes for the AT group and 60 minutes for the AT+DMM group. The two groups were asked to perform aerobic exercise at 60–75% of the maximum heart rate. Their fasting blood glucose (FBG) and serum cortisol levels were measured at the baseline and after six weeks. Results: Compared with the AT group, the group undertaking 6 weeks of aerobic training combined with slow, deep breathing exercises and mindfulness meditation showed significantly lower levels of FBG (p=0.001) and cortisol levels (p=0.01) than the AT group. Conclusion: The addition of slow deep breathing and mindfulness meditation to aerobic exercise can better control the glucose and cortisol levels of women with T2DM and thereby improve their outcomes and decrease their cardiometabolic risk.